Heterologous expression of bacterial natural product biosynthetic pathways. Issue 10 (8th January 2019) - Huo, Liujie; Hug, Joachim J.; Fu, Chengzhang; Bian, Xiaoying; Zhang, Youming; Müller, Rolf
Abstract : The review highlights the 2013–2018 literature on the heterologous expression of bacterial natural product biosynthetic pathways and emphasises new techniques, heterologous hosts, and novel chemistry. Abstract : Covering: 2013 to June 2018 Heterologous expression of natural product biosynthetic pathways is of increasing interest in microbial biotechnology, drug discovery and optimization. It empowers not only the robust production of valuable biomolecules in more amenable heterologous hosts but also permits the generation of novel analogs through biosynthetic engineering. This strategy also facilitates the discovery of novel bioactive compounds following the functional expression of cryptic biosynthetic gene clusters (BGCs) from fastidious original producers or metagenomic DNA in surrogate hosts, thus facilitating genome mining in the post-genomic era. This review discusses recent advances and trends pertaining to the heterologous production of bacterial natural products, with an emphasis on new techniques, heterologous hosts, and novel chemistry since 2013.